Performance metrics of a multirate resource sharing teletraffic model with finite sources under the threshold and bandwidth reservation policies. Issue 3 (1st May 2015) - Moscholios, Ioannis D.; Logothetis, Michael D.; Vardakas, John S.; Boucouvalas, Anthony C.
Abstract : The authors propose a new multirate teletraffic loss model of a single link with certain capacity that accommodates different service‐classes whose calls come from finite traffic sources. Calls compete for the available link bandwidth under the combination of the threshold (TH) and the bandwidth reservation (BR) policies. The TH policy can provide different quality of service among service‐classes by limiting calls of each service‐class up to a certain number, which is a predefined TH, which can be different for each service‐class. The BR policy reserves part of the available link bandwidth to benefit calls of high bandwidth requirements. They show that the proposed model, without the BR policy, has a product form solution (PFS) and prove recursive formulas for the efficient calculation of the call‐level performance metrics, such as time and call congestion probabilities as well as link utilisation. The combination of the TH and BR policies destroys the PFS of the model. However, they show that approximate but recursive formulas still exist for the efficient calculation of the call‐level performance metrics. The accuracy of the proposed formulas is verified through simulation and found to be very satisfactory.